CLINICAL CHARACTERISTICS OF PATIENTS WITH DENGUE FEVER: REPORT OF 48 PATIENTS IN 2010 - Mahboob, Atiya; Iqbal, Zafar; Javed, Rabil; Taj, Azeem; Munir, Asma; Saleemi, Munir Akhtar (Journal of Ayub Medical College Abbottabad, 2010)
Background: Dengue fever is a mosquito born viral disease. It occurs in tropical and sub-tropical areas of the world. Symptoms appear 3ˆ’14 days after the infective bite. Mortality can occur in dengue hemorrhagic fever and dengue shock syndrome unless prompt and adequate management is provided. Objective: To determine the clinical and epidemiological characteristics along with outcome of patients with dengue fever (DF) dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Design: Prospective, follow-up study. Place and duration of study: Department of Medicine, Shaikh Zayed Federal Postgraduate Medical Institute, Lahore from 3rd Oct 2010 to 20th Nov 2010. Patients and Methods: Specific serological tests for dengue fever were done in all 60 patients admitted with suspected diagnosis of DF, DHF and DSS. Forty-eight confirmed cases were evaluated for age, gender, clinical features and outcome of the disease. Results: Forty-eight out of 60 patients had positive serology for dengue fever. Male to female ratio was 1.09:1. Their ages ranged from 5 years to 68 years with the mean of 31.5±15.2 years. DF, DHF and DSS were found in 71%, 19% and 10% cases respectively. Common presentations were fever (100%), skin rash (83.33%), myalgia (69.75%), restlessness (66.67%) and rigors and chills (66.67%). All, except one patient improved clinically. One patient died on second day of admission. Conclusion: Dengue fever, a viral infection is re-emerging as a serious public health problem. Fever, rash, myalgia with rigors and chills were common presenting features. Keywords: Dengue fever, Dengue hemorrhagic fever, dengue shock syndrome, skin rash, epidemic